Identifikasi Budaya Tanaman Pakcoy (Brassica rapa L.) secara Hidroponik Sistem Nutriet Film Engineering (NFT) - Maskuri Maskuri; Cuci Cahyani; Devita Mustika Wulandari; Meliani Sulista (xxxx-xxxx, 2023)
Maskuri M, Cahyani C, Wulandari DM, Sulista M, Wibowo JA, Faras MI, Wahyudi S. 2022. Identification of plant cultivation (Brassica rapa L.) hydroponics engineering film nutrient system (NFT). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 274-282.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The pakcoy is one of the many horticultural plants of interest in the banyudistrict, but the availability of the land is not what is needed to cultivate. This survey is aimed at seeing how plant labor USES NFT's hydroponics system and analyzing the yield. The method used was interviews from direct observation to farmers. Using the NFT hydroponic system is one of the hydroponic methods with a minimal flow of water and a tilted slant on the installation module. Also, by using hydroponic farming systems, you can maximize narrow-to-yield yield. As for the results of plant cultivation with NFT's hydroponics system, one of which is the plant plants that grow faster. Moreover, the output of this system is larger than the size of the plant plants. From the standpoint of rooting control, it is also easier to reduce the risk of rooting down. Then maintenance is also more practical and requires less energy. Therefore, the average use of NFT's hydroponics system would be greater in maintenance, control, and plant production. Removing moss from a maximum hydroponic installation two times over a harvest would reduce the development of the moss in a paralytic pipet.